A NEUROEDUCATION-INFORMED DESIGN FOR A HYBRID LEARNING MODULE TO OPTIMIZE COGNITIVE LOAD AND MEMORY RETENTION - Lucy Lidiawati Santioso; Samat Yessentayev; Assel Zhanibek; Ayan Nurgaliyev (Yayasan Adra Karima Hubbi, 2025)
The growing complexity of hybrid learning environments demands instructional models that align with the cognitive architecture of the human brain. Excessive cognitive load and fragmented attention have become significant barriers to effective learning in digital and blended modalities. Neuroeducation—the interdisciplinary integration of neuroscience, psychology, and pedagogy—offers empirical insights for designing learning experiences that optimize working memory, enhance attention, and improve long-term retention. This study aims to develop and evaluate a neuroeducation-informed hybrid learning module that systematically manages cognitive load and facilitates memory consolidation among university students. A quasi-experimental design was employed with two groups: an experimental class using the neuroeducation-informed module and a control class using a conventional hybrid model. Participants included 80 undergraduate students enrolled in an educational psychology course. Data were collected through cognitive load scales, memory recall tests, and observational field notes, complemented by EEG-based attention tracking in a subsample. Quantitative data were analyzed using ANOVA, while qualitative data underwent thematic coding to identify engagement and retention patterns. The results indicated that the experimental group experienced significantly lower extraneous cognitive load (p < 0.01) and achieved higher delayed recall scores (M = 82.4) than the control group (M = 68.7). Students also reported improved focus, motivation, and conceptual understanding. The study concludes that integrating neuroeducation principles—such as chunking, spaced repetition, multimodal encoding, and emotional relevance—can substantially enhance hybrid learning effectiveness. The proposed framework bridges cognitive science and instructional design, contributing to sustainable innovation in higher education pedagogy.